Nonalcoholic steatohepatitis: the role of peroxisome proliferator-activated receptors - Francque, Sven; Szabo, Gyongyi; Abdelmalek, Manal F.; Byrne, Christopher D.; Cusi, Kenneth; Dufour, Jean-François; Roden, Michael; Sacks, Frank; Tacke, Frank (Nature reviews. Gastroenterology & hepatology, 2021)
The increasing epidemic of obesity worldwide is linked to serious health effects, including increased prevalence of type 2 diabetes mellitus, cardiovascular disease and nonalcoholic fatty liver disease (NAFLD). NAFLD is the liver manifestation of the metabolic syndrome and includes the spectrum of liver steatosis (known as nonalcoholic fatty liver) and steatohepatitis (known as nonalcoholic steatohepatitis), which can evolve into progressive liver fibrosis and eventually cause cirrhosis. Although NAFLD is becoming the number one cause of chronic liver diseases, it is part of a systemic disease that affects many other parts of the body, including adipose tissue, pancreatic β-cells and the cardiovascular system. The pathomechanism of NAFLD is multifactorial across a spectrum of metabolic derangements and changes in the host microbiome that trigger low-grade inflammation in the liver and other organs. Peroxisome proliferator-activated receptors (PPARs) are a group of nuclear regulatory factors that provide fine tuning for key elements of glucose and fat metabolism and regulate inflammatory cell activation and fibrotic processes. This Review summarizes and discusses the current literature on NAFLD as the liver manifestation of the systemic metabolic syndrome and focuses on the role of PPARs in the pathomechanisms as well as in the potential targeting of disease. This Review describes the pathophysiological roles of peroxisome proliferator-activated receptors (PPARs) in nonalcoholic steatohepatitis and related metabolic diseases, and summarizes the preclinical and clinical data on the use of PPAR agonists to treat nonalcoholic steatohepatitis as part of a systemic metabolic disease. Key points Nonalcoholic steatohepatitis (NASH) is the fastest growing liver disease worldwide; however, it is often not recognized until advanced disease stages. The management and treatment of NASH, the liver manifestation of the metabolic syndrome, require a holistic approach. Peroxisome proliferator-activated receptors (PPARs) regulate metabolism, inflammation and fibrosis, all of which determine NASH progression. There is an urgent need for medical therapy for patients with NASH. Both PPARα-β/δ dual agonism as well as PPARγ agonism have shown beneficial effects on liver histology in phase IIb clinical trials for NASH. Single, dual and pan-PPAR agonists are under development for the pharmacological treatment of NASH.